Design and implementation of an open source indexing solution for a large set of radiological reports and images. - Voet T; Devolder P; Pynoo B; Vercruysse J; Duyck P (Journal of Digital Imaging)
This paper hopes to share the insights we experienced during designing, building, and running an indexing solution for a large set of radiological reports and images in a production environment for more than 3 years. Several technical challenges were encountered and solved in the course of this project. One hundred four million words in 1.8 million radiological reports from 1989 to the present were indexed and became instantaneously searchable in a user-friendly fashion; the median query duration is only 31 ms. Currently, our highly tuned index holds 332,088 unique words in four languages. The indexing system is feature-rich and language-independent and allows for making complex queries. For research and training purposes it certainly is a valuable and convenient addition to our radiology informatics toolbox. Extended use of open-source technology dramatically reduced both implementation time and cost. All software we developed related to the indexing project has been made available to the open-source community covered by an unrestricted Berkeley Software Distribution-style license.